2020
DOI: 10.2147/hiv.s283184
|View full text |Cite
|
Sign up to set email alerts
|

<p>Level of Good Adherence on Option B+ PMTCT and Associated Factors Among HIV Positive Pregnant and Lactating Mothers in Public Health Facilities of Ilu Abba Bor and Buno Bedele Zones, Oromia Regional State, Southwestern Ethiopia, 2018</p>

Abstract: Background: PMTCT programs help safe delivery practices and recommended infant feeding, as well as providing ART for infants exposed to HIV after birth for prevention and effective treatment. PMTCT service helps to reduce about 1.4 million HIV infections among children between 2010 and 2018. This study aimed to assess the good adherence level and associated factors of option B+ PMTCT among HIV-positive pregnant and lactating women in public health facilities of Ilu Abba Bor and Buno Bedele zones, Oromia region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…According to this meta-analysis study, three primary articles [ 32 34 ] showed that social and financial support was positively associated with adherence to the Option B+ program. The odds of adhering to the Option B+ program were 3.44 times (AOR = 3.73, 95% CI: 2.12, 6.58) higher among those who received social and financial support when compared to their counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this meta-analysis study, three primary articles [ 32 34 ] showed that social and financial support was positively associated with adherence to the Option B+ program. The odds of adhering to the Option B+ program were 3.44 times (AOR = 3.73, 95% CI: 2.12, 6.58) higher among those who received social and financial support when compared to their counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Four primary articles reported that disclosure of HIV status to their partner was significantly associated with adherence to the Option B+ program [ 32 , 33 , 36 , 40 ]. Women who disclosed their HIV status to their partner were two times (AOR = 2.05, 95% CI: 1.75, 2.41) more likely to adhere to the Option B+ program than those women who had not disclosed their HIV status to their partner.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the studies, 20,31–35 involved only HIV‐positive pregnant women whereas the remaining six studies, 13,14,19,25,36,37 included both pregnant and lactating mothers living with HIV. Adherence was measured by the self‐report method in eight studies 13,14,19,20,32–35 . Whereas the remaining four studies employed both self‐report and pill count methods to measure adherence 25,31,36,37 .…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of included studies ranged from 103 31 to 350 14 . Six of the studies, 20,31–35 involved only HIV‐positive pregnant women whereas the remaining six studies, 13,14,19,25,36,37 included both pregnant and lactating mothers living with HIV. Adherence was measured by the self‐report method in eight studies 13,14,19,20,32–35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation